A Review of the Effect of Reading Engagement on Reading Achievement - Aihua Zhu; Samah Ali Mohsen Mofreh; Sultan Salem; Zhinan Li; Mao Yao (University of Bologna, 2023)
For decades, literacy research has placed a great deal of emphasis on reading engagement. It is widely acknowledged as a complex involving cognitive, behavioral, and emotional engagement. Learning engagement is an essential predictor of learning outcomes. It mediates educational intervention and learning outcomes. Although empirical studies proved the effectiveness of engagement on reading success, few studies have comprehensively reviewed the relationship between the subscales of engagement and how these subscales affect learning outcomes. To fill this gap, this review focused on exploring the interaction among subsets of engagement and how they affect reading achievement. The findings revealed that how engagement affects learning outcomes is determined by the intervention and how the outcomes are assessed and reported. The relationship between the engagement subscales is complicated: cognitive and behavioral engagement is a constant predictor of reading outcomes; emotion is the facilitator and affects behavioral or cognitive engagement. Behavioral engagement mediates cognitive engagement. Furthermore, learning outcomes could enhance emotional engagement, forming a natural learning cycle. This model is significant in understanding how learning engagement affects learning outcomes. It also demonstrated how the engagement subscales interacted and worked together to facilitate learning outcomes.